The examination of shock wave attenuation in running shoes - Lloyd, S.; Wu. T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Various sports footwear companies have produced different types of running shoes to "mimic" barefoot walking or running such as FiveFingers and Rush shoes. There is limited evidence suggesting these shoes are able to reduce vertical ground reaction forces while standing, walking or running. The purpose of this study was to examine the vertical ground reaction forces between the minimalist shoes and traditional well-cushioned shoes. All shoes underwent both static and dynamic performance testing on top of an AMTI force platform. The results indicated that the Vibram minimalist shoe provided the highest amount of vertical ground reaction forces during the dynamic testing but the lowest amount of vertical ground reaction forces during the static testing. The study provides a preliminary understanding of vertical ground reaction forces in minimalist running shoes.